Development of CytoAcademy: a new web- and mobile-based E-learning platform for cytopathologists and cytotechnologists by the Korean Society for Cytopathology in the post-pandemic era - Ran Hong; Yosep Chong; Seung Wan Chae; Seung-Sook Lee; Gyungyub Gong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Since the late 1990s, online e-learning has offered unparalleled convenience and affordability, becoming increasingly popular among pathologists. Traditional learning theories have been successfully applied to web/mobile-based learning systems, with mobile technologies even enhancing conventional offline education. In cytopathology, hands-on microscope training has traditionally been paramount, complemented by real-case presentations and lectures. However, the coronavirus disease 2019 (COVID-19) pandemic disrupted regular academic activities, making online e-learning platforms essential. We designed a web/mobile-based learning platform to enhance continued medical education in cytopathology at various levels, particularly during the era of COVID-19 and beyond. Since 2021, we have integrated curriculum materials, virtual education files, and whole-slide images (WSIs) of cytopathology, submitted from over 200 institutions across Korea, with the support of numerous instructors. We develop a new e-learning platform named "CytoAcademy" composed of a basic session for each organ and level across the range of morphologic findings; on-demand lectures to enhance cytopathologic knowledge; WSI archives that allow users to explore various histologically confirmed cases; and a self-assessment test to help organize diagnostic knowledge acquired through the web/mobile-friendly learning system. The platform provides not just an opportunity to achieve a correct diagnosis, but also a learning experience based on problem-solving point. Members interact, identify their deficiencies, and focus on specific educational materials. In this manner, all participants can actively engage in creating and maintaining knowledge and foster a proactive approach to learning.